KORELASI ANTARA MINAT DAN KEAKTIFAN SISWA DENGAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK KELAS III - Andry Hariyani; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the correlation between student interest and activity with learning outcomes in thematic learning in class III SDN 16 Pontianak City. The method used is a descriptive method with a quantitative approach. The population and sample in this study were all students of class IIIA, amounting to 22 students. Data collection techniques in this study are direct observation techniques, indirect observations and documentary studies. The data collection instruments used were questionnaires and documentation of daily test scores of subthemes 1,2, and 3 themes 2. The results showed that interest in learning in class IIIA SDN 16 Pontianak City was 87.06% in the "Very Good" category, Student learning activity was 89.35% in the "Very Good" category, and student learning outcomes on the average daily test score of 73.76 were included in the "Good Enough" category. Based on the results of statistical calculations calculated using the double correlation formula, the correlation between student interest and activity with learning outcomes obtained rcount of 0.327, while rtable of 0.423 which means rcount < rtable or (0.327 < 0.423). Based on the results of this study, the relationship between students' interest and activity with learning outcomes in class III thematic learning at SDN 16 Pontianak City is in the low category so it is considered uncorrelated.